1989
DOI: 10.1016/0014-5793(89)80957-3
|View full text |Cite
|
Sign up to set email alerts
|

The noncompetitive blocker [3H]chlorpromazine labels segment M2 but not segment M 1 of the nicotinic acetylcholine receptor α‐subunit

Abstract: The membrane bound acetylcholine receptor from Torpedo marmorata was photolabeled by the noncompetitive channel blocker [~H]chlorpromazine under equilibrium conditions in the presence of the agonist carbamoylcholine. The radioactivity incorporated into the AChR subunits was reduced by addition of phencyclidine, a specific ligand for the high-affinity site for noncompetitive blockers. The ~t-subunit was purified and digested with trypsin and/or CNBr and the resulting fragments fractionated by HPLC. Sequence ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 33 publications
3
47
0
1
Order By: Relevance
“…The affinity-labelling data obtained with [ 3 H]chlorpromazine (Giraudat et al , 1987(Giraudat et al , 1989Revah et al 1990) and TPMP , thus support the view that: (1) .DSG-EK MTLSISVLLSLTVFLLVIV E..…”
Section: The Mil Segment Is a Component Of The Ion Channelsupporting
confidence: 72%
See 1 more Smart Citation
“…The affinity-labelling data obtained with [ 3 H]chlorpromazine (Giraudat et al , 1987(Giraudat et al , 1989Revah et al 1990) and TPMP , thus support the view that: (1) .DSG-EK MTLSISVLLSLTVFLLVIV E..…”
Section: The Mil Segment Is a Component Of The Ion Channelsupporting
confidence: 72%
“…Labelling of #-Ser262 is blocked by phencyclidine and belongs to the hydrophobic segment Mil, thus pointing to Mil as part of (or in the close vicinity to) the high-affinity site for non-competitive blockers within the ion channel . Similar experiments were repeated with the other subunits and sequence analysis resulted in the identification of Ser254 and Leu257 for the /?-subunit (Giraudat et al 1987), Ser248 for the a-subunit (Giraudat et al 1989) and Thr253, Ser257 and Leu26o for the y-subunit (Revah et al 1990) as residues labelled by [ 3 H]chlorpromazine in a phencyclidine sensitive manner. Following the finding of Giraudat et al (1986) with chlorpromazine, Oberthiir et al (1986) using triphenylmethylphosphonium (TPMP) have also identified £-Ser262 as the labelled amino acid.…”
Section: The Mil Segment Is a Component Of The Ion Channelmentioning
confidence: 96%
“…Importantly, a highly conserved aromatic residue of the β8-β9 loop, namely, Trp in cationic receptors (W160 in ELIC) or Phe/Tyr in anionic receptors, forms part of the conserved GEW sequence motif, which was previously demonstrated to be implicated in the positive allosteric modulation of the neuronal α7 nAChR by regulatory Ca 2+ ions (65). This β8-β9 loop site is distinct from the widely known pore blocker site of CPZ, which has been extensively studied in the Torpedo nAChR using electrophysiological, mutagenesis, and photoaffinity labeling studies (16,(45)(46)(47)(48)(49)(50). In the present study, we could not observe CPZ binding in the ELIC pore, and this can be likely explained by the unusual and bulky Phe residue at the 16′ pore position in ELIC, which prevents pore access to noncompetitive pore blockers such as memantine (40) and probably also CPZ.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, [ 3 H]CPZ became a widely used tool to probe the channel pore of nAChRs in closed, open, and desensitized states (16,(45)(46)(47)(48)(49)(50). Initial photoaffinity labeling studies on the Torpedo nAChR in the desensitized state revealed that CPZ binds to a high-affinity binding site near the cytoplasmic end of the channel pore, comprising the 2′, 6′, and 9′ positions of the pore-lining M2-helix (46)(47)(48)(49). Recently, Chiara et al (50) extended on these observations and identified an additional binding site in the desensitized state for [ 3 H]CPZ near the extracellular end of the channel pore, comprising the 16′, 17′, and 20′ positions of the M2 segment.…”
mentioning
confidence: 99%
“…The primary and secondary structure of the MSRs may be crucial for the gating and permeation properties of the channel. Most of the studies that combine pharmacological, biochemical, site-directed mutagenesis and electrophysiological data on MSRs have focused on M2 (Giraudat et al, 1986(Giraudat et al, , 1987(Giraudat et al, , 1989Hucho, Oberthur & Lottspeich, 1986;Imoto et al, 1986Imoto et al, , 1988Imoto et al, , 1991Charnet et al, 1990;Villaroel, Herlitze & Sakmann, 1991;Pedersen et al, 1992;White & Cohen, 1992). The M2 and M1 segments from each subunit associate around a central axis to form part of the aqueous ion channel.…”
Section: Introductionmentioning
confidence: 99%